Study on Stress Corrosion Sensitivity of 304 and 304L in the Ethylene Oxide/Ethylene Glycol Unit of a Certain Refinery - TANG Zhenhua, LIU Xiwu, LI Hui, LIU Xuxia, ZHANG Ruoxi (Cailiao Baohu, 2024)
Ethylene oxide (EO) is a crucial organic synthesis raw material，ranking just behind polyethylene and polyvinyl chloride，and is primarily used in the production of ethylene glycol (EG).The SD process for EO/EG units(a patented EO/EG technology from SD Company in the United States) suffers from typical stress corrosion problems.To address this，the corrosion behavior and mechanisms of refinery-grade 304 and 304L materials in typical environments such as EO purification towers were simulated.Stress corrosion cracking susceptibility of the two materials was evaluated through slow strain rate testing.Results showed that the stress corrosion in EO/EG units was associated with the sensitization of stainless steel，with sensitized 304 and 304L stainless steel exhibiting susceptibility to stress corrosion cracking.Corresponding measures for material and process optimization were proposed，providing technical support to enhance the safe and stable operation of EO/EG units.